Penerapan Disiplin dan Penegakan Hukum Protokol Kesetahan sebagai Upaya Membangun Kesadaran Hukum Masyarakat di Kota Makassar - Al Hamzir Aqbar; Muhammad Akbal; Andika Wahyudi Gani (Universitas Negeri Makassar, 2022)
This study aims to examine 1) The implementation of Makassar Mayor Regulation No. 51 of 2020 concerning the Implementation of Discipline and Law Enforcement of Health Protocols in Makassar city, 2) The public responses to the application of Discipline and Law Enforcement of Health Protocols in Makassar city, and 3) The determinant factors in the implementation of Makassar Mayor Regulation no. 51 of 2020 concerning the Implementation of Discipline and Law Enforcement of Health Protocols in Makassar city. The method of the study used was a qualitative research type with a descriptive approach. Data collection techniques employed observation, interviews, and documentation; then, analyzed by using triangulation technique. The results of the study reveal that 1) The implementation of Makassar Mayor Regulation No. 51 of 2020 concerning the Implementation of Discipline and Law Enforcement of the Security Protocol in Makassar City has not been optimal. It is due to the implementation of communications such as socialization, monitoring, and the implementation of sanctions that are not maximized, 2) The public response to the implementation of discipline and law enforcement of health protocols in Makassar city is not all people gave a good response to the regulation. The community compliance is caused because they are afraid of sanctions, desire to maintain relationships around them, and have an understanding that what is applied to common safety. Meanwhile, people's disobedience is caused by their lack of understanding of the dangers and impacts caused by the Covid-19 virus, 3) The determinant factors in the implementation of Makassar Mayor Regulation No. 51 of 2020 concerning the Implementation of Discipline and Law Enforcement of Health Protocols in Makassar City are the supporting and inhibiting factors. The supporting factors are the cooperation of officers in handling Covid19, the support from several parties, and adequate facilities and infrastructure; whereas, the inhibiting factors are the socialization does not reach all levels of society, the implementation of sanctions are still selective, and the use of new terms that is difficult for some people to understand.